Conversational Implicature Analysis in “Turning Red” Movie Script - Ni Kadek Diah Darmayani; I Gusti Ayu Gde Sosiowati; I Gusti Agung Istri Aryani (CV. Ulil Albab Corp, 2023)
This study aims to analyze the conversational implicature in the Disney movie, Turning Red which was released in March 2022. The theory is using conversational implicature proposed by Grice (1989) to identify the types of implicature namely Generalized Conversational Implicature and Particularized Conversational Implicature and its implied meaning. This research uses qualitative descriptive method. The data was taken in the form of phrases. The results showed that there were 18 implied conversational data found in conversations that occurred between characters in the film, 10 data classified as generalized conversational implicature, meanwhile, 8 data found in a particularized type of conversational implicature with their implied meaning analysis from the context of situation.